Tributaç\~ao sobre gastos com saúde das famílias e do sistema único de saúde: Avaliaç\~ao da carga tributária sobre medicamentos, material médico-hospitalar e próteses/órteses - Luís Carlos Garcia de Magalh\~aes; Frederico Andrade Tomich; Fernando Gaiger Silveira; Salvador Teixeira Werneck Vianna; Leandro Safatle; Alexandre Batista de Oliveira; Rodrigo Dourado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– The main objective of this study is the determination of the indirect tax burden which is applied to Brazilian health sector. This requires the estimation of tax incidence over household expenses, as well of those made by public sector, which includes medical institutions and hospitals. Regarding the case of households, the basic aim was to evaluate the weight of indirect taxation in the purchases of drugs and medications, analysing it regionally and in terms of income classes. This has been done with the individualised data ("microdata") of IBGE's Household Budgets Research (POF), 1995-96. In what concerns to the public sector, the informations related to acquisitions of drugs and medications, hospital material and orthesis and prostheses have been extracted from the databases of Brazilian Health System (DATASUS). The tax rates applied for both cases were calculated taking into account the effective legal structures, including eventual differentiated treatments and exemptions, defined by the Federal Revenue Secretary (SRF) and the Finance Secretaries of Brazilian states. The obtained results point unequivocally to a great importance of indirect taxation in the final composition of the researched products prices. The average tax burden which falls upon the purchases of drugs and medications made by households varies among 21% and 26%, according to the state and the existence or not of imported components in the production. There's an obvious regressivity aspect in this situation, which is still worsened by the degree of essentiality of the involved goods and by the disparity in the national income distribution. In the case of the public sector (SUS), it was verified that there's an expressive fiscal cost, nearby R 1 billion, which relapses over its expenses. Therefore, indirect taxation structure, the way which is now constituted, do represent undoubtedly an important factor to press the costs of the public health system in Brazil.
Keywords: 330